German S2k-guideline on diagnostics, treatment and surveillance of low-grade appendiceal mucinous neoplasms (LAMN) - Köhler-Dauner, Franziska; Arnold, Dirk; Aust, Daniela E.; Betge, Johannes; Brecht, Ines B.; Germer, ChristophThomas; Grouven, Bernd; Harter, Philipp; KasperVirchow, Stefan; Koslowski, Kai; Neeff, Hannes Philipp; Neumann, Jens; et al. (European journal of cancer, 2025)
The German guideline for low-grade appendiceal mucinous neoplasms (LAMN) and pseudomyxoma peritonei (PMP) offers comprehensive recommendations for diagnosis, treatment, and surveillance of these rare tumours. Developed by the German Society of General and Visceral Surgery (DGAV) alongside 14 other medical societies or task groups, this S2k-guideline addresses the need for standardised care in the absence of high-quality randomized controlled trials due to the rarity of LAMN and PMP. The guideline covers classification and staging of LAMN according to WHO and TNM systems, emphasising histological analysis and surgical protocols aimed at preventing intra-abdominal perforation. Diagnostic recommendations include imaging (MRI or CT) and preoperative tumour marker assessment, along with screening colonoscopies to rule out synchronous colorectal malignancies in specific age groups. Therapeutic guidelines focus on the importance of treatment in specialised centres with expertise in cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). CRS combined with HIPEC is recommended for patients with PMP, with an emphasis on multidisciplinary team involvement and psycho-oncological support. The guideline outlines post-treatment surveillance, recommending six-monthly imaging and tumour marker evaluations for five years. It highlights the importance of considering fertility preservation in patients undergoing cytoreductive surgery and HIPEC. This consensus-based guideline aims to enhance the quality and consistency of care for patients with LAMN and PMP, offering a structured approach despite limited clinical trial data.